Implementation of IOT Automatic Controlling System and Android Franchise System in Oyster Mushroom MSMEs in Gintangan Village To Be Globally Competitive in the Digital Economy Era - Raup Padillah; Fitri Nurmasari; Siti Napisah; Heriberthus Wicaksono (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
MSMEs are one of the business units that play an important role in the growth and development of the economy in Indonesia, especially in lower and middle class society. The MSME "Sunawan Mushroom" which is a partner in this community service program is one of the MSMEs in Rogojampi District, Banyuwangi, engaged in the oyster mushroom cultivation business. Based on the results of the identification of the proposing team in partner businesses, there are two main problems, namely in the areas of production and marketing. The community service program which was carried out for 8 months attempted to overcome these two problems. This activity is in accordance with the main performance indicators (IKU) of PGRI Banyuwangi University, namely that lecturers carry out activities outside the campus and the results of the lecturers' work are used by the community. Because this activity involves students, this activity is also in accordance with one of the IKUs, namely students gaining experience outside campus. The outputs targeted by this program include IoT-based Automatic Controlling System Technology, an Android-based franchise system, increasing partner production and sales, and increasing partner turnover. Overall, the technology implemented in the partner's oyster mushroom business succeeded in increasing production capacity by 25% (from 500kg to an increase of 650kg), succeeded in reducing the level of pest attacks during the mushroom growing process from 15% to 5% (down 10%), and reduced fungus death rate 5-10%. These results automatically increase partners' income from sales of oyster mushrooms by optimizing the temperature conditions of mushroom cages and minimizing the death rate of oyster mushrooms from pest attacks that attack mushroom tanks.